Coccidiosis Disease in Cattle in Indonesia and Development of Diagnostic Techniques - Fitrine Ekawasti; April H Wardhana (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2019)
Coccidiosis is a parasitic disease caused by the protozoan of the order Coccidia, the family Eimeriidae of the genus Eimeria which breeds rapidly in the digestive tract and is the most difficult disease to be controlled on cattle farms. Eimeria spp. in cattle can cause high economic losses and increase susceptibility against infectious diseases. Therefore, coccidiosis in cattle needs attention from the government. This paper reviews a number of diagnostic methods that can be used in the detection of Eimeria spp. in cattle based on the goals and objectives of the examination. The coccidiosis cases often do not show any clinical symptoms but can cause sudden death in livestock. The diagnostic method that still used at present is based on its morphology that should not be used in identifying Eimeria species because the morphological characteristics Eimeria spp. have similar shape and size structures between species (resembling morphology). An appropriate diagnostic method for Eimeria is needed in the context of controlling coccidiosis strategically.